Medical Image Computing and Computer-Assisted Intervention – MICCAI 2017 : 20th International Conference, Quebec City, QC, Canada, September 11-13, 2017, Proceedings.: 20th International Conference, Quebec City, QC, Canada, September 11-13, 2017, Proceedings. Part III (2017) - Unknown
No abstract available